1989
DOI: 10.1007/bf01389047
|View full text |Cite
|
Sign up to set email alerts
|

Nonvanishing ofL-functions for GL (2)

Abstract: Given an L-function and a point in the complex plane, one sometimes needs to know that one can twist the L-function by a character of finite order so that the twisted L-function does not vanish at the given point. This problem arises for example in Shimura's theory [16] where m is an integer in the critical range, f is a primitive Hilbert modular form, and ~k is a ray class character. Shimura's theory proceeds along the following lines: First an algebraicity theorem is proved for the special values of certain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
59
0

Year Published

1989
1989
2013
2013

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(62 citation statements)
references
References 15 publications
3
59
0
Order By: Relevance
“…This was proved by Rohrlich [115] using several non-trivial results as input, not the least of which was a version of the Bombieri-Vinogradov theorem over number fields due to Murty and Murty [101]. Very roughly, one takes m to be a product of prime ideals p such that N(p) − 1 has no large prime factor.…”
Section: Techniques Over Number Fieldsmentioning
confidence: 99%
“…This was proved by Rohrlich [115] using several non-trivial results as input, not the least of which was a version of the Bombieri-Vinogradov theorem over number fields due to Murty and Murty [101]. Very roughly, one takes m to be a product of prime ideals p such that N(p) − 1 has no large prime factor.…”
Section: Techniques Over Number Fieldsmentioning
confidence: 99%
“…Toute copie ou impression de ce fichier doit contenir la présente mention de copyright. [1,3,7,9,10,11,13,15,17] and the references given there. This is of interest in various aspects such as the Birch-Swinnerton-Dyer conjecture, the Siegel zero (see [7]) and the theory of modular forms of half-integral weight (see [16,18] [12].…”
mentioning
confidence: 99%
“…With such motivation, Shimura [14] showed that given a weight k modular form ƒ, there is some character of finite order x such that L(l, ƒ,#) is not zero. This was refined by Rohrlich [13], who proved that for ƒ an arbitrary automorphic form on PGL(2) and for arbitrary s, there exists a character x of finite order such that L(s,f,x) ¥" 0.…”
mentioning
confidence: 98%